2017
DOI: 10.1186/s12885-017-3297-2
|View full text |Cite
|
Sign up to set email alerts
|

The E2F4 prognostic signature predicts pathological response to neoadjuvant chemotherapy in breast cancer patients

Abstract: BackgroundNeoadjuvant chemotherapy is a key component of breast cancer treatment regimens and pathologic complete response to this therapy varies among patients. This is presumably due to differences in the molecular mechanisms that underlie each tumor’s disease pathology. Developing genomic clinical assays that accurately categorize responders from non-responders can provide patients with the most effective therapy for their individual disease.MethodsWe applied our previously developed E2F4 genomic signature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…We investigated the association between the RPS and characteristics of the ER-positive tumor microenvironment, as well as between the TNBC-RPS and characteristics of the TNBC tumor microenvironment respectively (Figure 6). Of note, the RPS identified changes in the tumor cell proliferation rate and immune cell infiltration in ER-positive patients, which was supported by previous studies showing that the cell-cycle-related 16,[64][65][66] and immune-infiltration-related gene signatures [67][68][69] were associated with responsiveness. This observation could be further validated through the prediction performance of the 143 predictive gene signatures.…”
Section: Discussionsupporting
confidence: 79%
“…We investigated the association between the RPS and characteristics of the ER-positive tumor microenvironment, as well as between the TNBC-RPS and characteristics of the TNBC tumor microenvironment respectively (Figure 6). Of note, the RPS identified changes in the tumor cell proliferation rate and immune cell infiltration in ER-positive patients, which was supported by previous studies showing that the cell-cycle-related 16,[64][65][66] and immune-infiltration-related gene signatures [67][68][69] were associated with responsiveness. This observation could be further validated through the prediction performance of the 143 predictive gene signatures.…”
Section: Discussionsupporting
confidence: 79%
“…The finding that current adjuvant treatments cannot improve the prognosis of patients exhibiting high expression of this E2F4 signature also agrees with our results that only CDK4/6 inhibition, and not chemotherapy nor fulvestrant, is able to suppress completely E2F4 target gene expression. However, the same authors reported that high levels of the 199-gene E2F4 signature are predictive of pathological complete response to neoadjuvant chemotherapy in ER+ breast cancer (43). Although this might seem contradictory, transcriptional activity of E2F4 is a marker of highly proliferative tumors, which is a recognized predictive factor of an initial response to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In MDA-MB-231 Met-DOX cells, metformin upregulated GADD45B, which is a stress-sensor and apoptosis-regulator and contributes to CDKN1A upregulation, induction of apoptosis and G2/M-phase enrichment 46 . Furthermore, metformin also upregulated E2F4 in both MCF-7 and MDA-MB-231 Met-DOX cells, which plays a key role in the suppression of proliferation-associated genes 37 . In relation to the effects of metformin on AR 49 , showed that its expression appears to play a different prognostic role in breast cancer positive and negative for estrogen receptors (ER).…”
Section: Discussionmentioning
confidence: 94%